Using Artificial Intelligence to Read and Understand Letters Or Orders Received at the University and Intelligently Direct Them to Departments (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
This article presents the opinions of domestic and foreign scientists on using artificial intelligence to read and understand letters or orders received at universities and intelligently direct them to departments. Using AI to read and understand letters or orders received at a university and intelligently direct them to the appropriate departments is a great use of natural language processing (NLP) and automation. Using artificial intelligence to read and understand letters or orders received at a university and then intelligently direct them to the appropriate departments can streamline operations, improve efficiency, and reduce human error.